Polyamide composite cross-section fiber, polyamide multifilament, and polyamide composite cross-section false twist textured yarn

By controlling the orientation parameters and crystallinity of polyamide composite cross-section fibers, the issues of poor wear resistance and crimping performance in existing fibers are addressed, resulting in fibers with enhanced abrasion resistance and soft stretchability.

JP7648000B2Active Publication Date: 2025-03-18TORAY INDUSTRIES INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024508585
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-27
Filing Date
2024-01-19
Publication Date
2025-03-18
Estimated Expiration
2044-01-19

AI Technical Summary

Technical Problem

Existing polyamide composite cross-section fibers suffer from poor wear resistance due to uncontrolled orientation properties, leading to reduced abrasion resistance and crimping performance compared to polyamide alone fibers.

Method used

The development of polyamide composite cross-section fibers with specific orientation parameters, crystallinity ranges, and composite forms (side-by-side or eccentric core sheath types) to enhance wear resistance and crimping properties.

Benefits of technology

The controlled orientation characteristics of the fibers result in polyamide composite cross-section fibers with excellent abrasion resistance and crimping performance, achieving superior soft stretchability and wear resistance compared to conventional fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648000000007
    Figure 0007648000000007
  • Figure 0007648000000008
    Figure 0007648000000008
  • Figure 0007648000000009
    Figure 0007648000000009
Patent Text Reader

Abstract

The present invention addresses the problem of providing, by appropriately controlling alignment characteristics of fibers, polyamide composite cross-section fibers having both excellent crimp characteristics and abrasion resistance which have been difficult to be achieved by conventional technologies. The present invention pertains to polyamide composite cross-section fibers containing two types of polyamide satisfying the following terms A-C. A. The form of composite of the fiber cross-section of the polyamide composite cross-section fibers is a side-by-side type or an eccentric core-sheath type. B. The absolute value of the difference in an alignment parameter between the two types of polyamide is 0.20 or more. C. The range of the alignment parameter of the polyamide on the less aligned side is 1.50-3.00.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyamide conjugated cross section fiber having excellent crimping properties with excellent soft stretchability when made into a fabric, and also provides a polyamide conjugated cross section fiber having greatly improved crimping properties with respect to abrasion resistance. [Background technology]

[0002] Polyamide fibers, such as polycaproamide and polyhexamethylene adipamide, are widely used not only for clothing applications but also for interior and vehicle interiors and industrial applications due to their excellent mechanical properties and dimensional stability.

[0003] Among these, false twist textured yarns in which polyamide fibers have been given crimping properties are particularly suitable for use in producing stretchable woven and knitted fabrics. However, it is difficult to obtain woven and knitted fabrics with good stretchability by subjecting polyamide fibers alone to false twist textures, etc. Therefore, methods have been proposed in which two types of polyamides with different compositions are bonded side-by-side in the fiber cross section or combined in an eccentric core-sheath type to produce polyamide composite cross-section fibers, thereby giving crimping properties to polyamide fibers and producing stretchable woven and knitted fabrics.

[0004] For example, there have been proposed polyamide composite cross-section fibers in which two types of crystalline polyamides with different compositions are combined in an eccentric core-sheath structure and the water absorption and heat shrinkage stress are specified (Patent Document 1), and polyamide composite cross-section fibers in which two types of polyamides with different viscosities are combined in a side-by-side or eccentric core-sheath structure and the CF value is specified (Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2021 / 020354 [Patent Document 2] Japanese Patent Application Publication No. 2018-3190 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the polyamide composite cross-section fiber described in Patent Document 1, in which two types of crystalline polyamides with different compositions are composited in an eccentric core-sheath type, has a problem that the fiber orientation characteristics necessary for abrasion resistance are not appropriately controlled, resulting in inferior abrasion resistance when made into a fabric. In particular, compared with polyamide single fibers, although both are the same crystalline polyamide, they are simply laminated together with different compositions, so peeling and the like is unavoidable, which is one of the factors that significantly reduces abrasion resistance.

[0007] The polyamide composite cross section fiber described in Patent Document 2, in which two types of polyamides with different viscosities are composited in a side-by-side or eccentric core-sheath configuration, also has the same problem of inferior abrasion resistance as the polyamide composite cross section fiber described in Patent Document 1. It is true that abrasion resistance may be improved when polyamides with the same composition are bonded together only because the viscosity is different, but this is only true for polyamide composite cross section fibers, and the abrasion resistance is inevitably inferior to that of polyamide fibers alone.

[0008] An object of the present invention is to provide a polyamide bicomponent cross-section fiber that is excellent in both abrasion resistance and crimp properties, which was difficult to achieve with conventional techniques, by appropriately controlling the fiber orientation characteristics necessary for abrasion resistance. [Means for solving the problem]

[0009] In order to achieve the above object, the present invention employs the following configuration. (1) A polyamide bicomponent cross-section fiber made of two types of polyamides, which satisfies the following items A to C: A. The composite form of the fiber cross section of the polyamide composite cross section fiber is a side-by-side type or an eccentric core-sheath type. B. The difference in orientation parameters between the two polyamides is 0.20 or more in absolute value. C. The orientation parameter of the low-oriented polyamide is in the range of 1.50 to 3.00. (2) The polyamide fiber with bicomponent cross section according to (1) above, wherein the crystallinity of the polyamide on the less oriented side is in the range of 10.0 to 40.0%. (3) A polyamide multifilament comprising the polyamide bicomponent cross section fiber according to (1) or (2) above, having a stretch elongation of 1.0% or more. (4) A polyamide composite cross-section false twist textured yarn consisting of two types of polyamide, which satisfies the following items D to G. D. The composite form of the fiber cross section of the polyamide composite cross section false twist textured yarn is a side-by-side type or an eccentric core-sheath type. E. The polyamide composite cross section false twist textured yarn has a stretch elongation of 30.0% or more. F. The difference in orientation parameters between the two polyamides is 0.05 or more in absolute value. G. The crystallinity of the low-oriented polyamide is in the range of 10.0 to 40.0%. Effect of the Invention

[0010] According to the present invention, by appropriately controlling the orientation characteristics of the fibers, it is possible to provide a polyamide bicomponent cross section fiber that is excellent in both abrasion resistance and crimp properties. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 shows an example of the cross section of the polyamide composite cross section fiber of the present invention, where (A) to (C) are schematic diagrams of a side-by-side type. [Diagram 2] FIG. 2 shows an example of the cross section of the polyamide composite cross section fiber of the present invention, and is a schematic diagram of an eccentric core-sheath type. [Diagram 3] FIG. 3 is a schematic diagram illustrating the degree of eccentricity of the eccentric core-sheath type in an example of a cross section of a polyamide composite cross section fiber of the present invention. [Figure 4]FIG. 4 illustrates the composite interface of the extruded yarn and the direction of yarn cooling air in an example of a method for producing a polyamide composite cross-section fiber of the present invention, where (A) is a schematic diagram showing an example of the present invention, and (B) is a schematic diagram showing an example of the production method described in Japanese Patent No. 3769434 (Japanese Patent Laid-Open No. 2000-328349). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below.

[0013] The polyamide composite cross-section fiber according to an embodiment of the present invention (hereinafter also referred to as the "present embodiment") is made of two types of polyamide. From the viewpoint of abrasion resistance, it is important that both types of polyamide are polyamide to increase the affinity of the composite interface and suppress interfacial peeling. The polyamide in this embodiment is a polymer in which so-called hydrocarbons are linked to the main chain via amide bonds. Examples of polyamides include polycaproamide, polyundecane amide, polydodecane amide, polytetramethylene adipamide, polypentamethylene adipamide, polypentamethylene sebacamide, polyhexamethylene adipamide, polyhexamethylene sebacamide, polyhexamethylene dodecane amide, polyhexamethylene tridecane amide, and copolymers containing them as main components. Here, the main component means that it is 50 parts by mass or more in 100 parts by mass of the copolymer.

[0014] The above two types of polyamides are not limited as long as there is a difference in the degree of orientation, i.e., a difference in the orientation parameter. The above two types of polyamides may be of the same composition or different compositions, but in order to obtain the desired crimping properties, polyamides of different compositions are preferred, such as polyamides composed of aminocaproic acid units, such as polycaproamide, and polyamides composed of dicarboxylic acid and diamine units, such as polyhexamethylene sebacamide. When the composite cross-section fiber is composed of polyamides of the same composition, it is sufficient to make the polymerization degrees of the two different in order to obtain the desired crimping properties.

[0015] Examples of the composite form of the fiber cross section include a side-by-side type, an eccentric sheath-core type, a double sheath-core type, an island-in-the-sea type, and a multi-layer laminate type. From the viewpoint of obtaining a desired crimping property, the polyamide composite cross section fiber of this embodiment is either a side-by-side type or an eccentric sheath-core type. In the composite form of the polyamide composite cross section fiber of this embodiment, the side-by-side type refers to a composite form as shown in FIG. 1, and the eccentric sheath-core type refers to a composite form as shown in FIG. 2. When the above two polyamides are polyamide (A) and polyamide (B), in the side-by-side type, the composite interface (lamination surface) of polyamide (A) 1 and polyamide (B) 2 may be straight as shown in FIG. 1 (A), or may be curved as shown in FIG. 1 (B) and FIG. 1 (C). In either the side-by-side type or the eccentric sheath-core type, the composite ratio of the two polyamide components is preferably in the range of 2:1 to 1:2 in terms of the cross-sectional area ratio. Regarding the eccentric sheath-core type, the degree of eccentricity of the eccentric sheath-core type as shown in FIG. 2 composed of a polyamide (A) 3 as a core component and a polyamide (B) 4 as a sheath component is preferably in the range of L / M from 1 / 8 to 1 / 2, where L is the line segment between the center 6 of the composite cross section fiber and the center 5 of the core component as shown in FIG. 3 and M is the line segment between the intersections of the extended line segment L and the outer periphery of the composite cross section fiber.

[0016] In the polyamide composite cross section fiber of this embodiment, it is extremely important from the viewpoint of abrasion resistance to appropriately control the orientation characteristics. The polyamide composite cross section fibers described in Patent Documents 1 and 2 do not appropriately control this, so even though they have good crimp performance, they have poor abrasion resistance. There are various methods for measuring the orientation characteristics of fibers, but the orientation characteristics of the polyamide composite cross section fiber of this embodiment refer to orientation parameters measured and normalized by laser Raman spectroscopy, and the gist of them is described below.

[0017] Polyamide 1640cm -1The Raman band around is attributed to the stretching vibration mode of C=O, whose stretching vibration direction is perpendicular to the molecular chain, and shows a change in polarizability in the direction perpendicular to the molecular chain direction. Raman scattering is strong when the stretching vibration direction of the molecular chain and the polarization direction of the incident light are the same. Therefore, the Raman scattering intensity I 1640 changes in correlation with the degree of orientation. In other words, the ratio of the Raman scattering intensity with perpendicular polarization to the Raman scattering intensity with parallel polarization is a parameter for evaluating the degree of orientation. -1 Raman scattering intensity I 1450 By using vertically polarized light and parallel polarized light as the standard, the Raman scattering intensity for each polarization condition (vertical / parallel) can be normalized as an orientation parameter. The orientation parameter increases as the degree of orientation along the fiber axis increases, and is 1.0 (minimum value) in the case of no orientation (uniform orientation). The formula is shown below. Orientation parameter = (I 1640 / I 1450 ) Vertical polarization / (I 1640 / I 1450 ) Parallel polarization

[0018] The above formula satisfies the following definitions: Vertical condition: The fiber length direction and the polarization direction are perpendicular Parallel condition: The fiber longitudinal direction and the polarization direction are parallel I 1640 Vertical: 1640cm when vertical -1 Intensity of the Raman bands I 1450 Vertical: 1450cm when vertical -1 Intensity of the Raman bands I 1640 Parallel: 1640cm when parallel -1 Intensity of the Raman bands I 1450 Parallel: 1450cm when parallel -1 Intensity of the Raman bands

[0019] The orientation parameters will be explained in detail in the Examples.

[0020] In the polyamide composite cross section fiber of this embodiment, the difference between the orientation parameters of the two polyamides is 0.20 or more in absolute value, preferably 0.30 or more. By setting it in this range, the crimping performance of the fiber becomes good, and a fabric or fiber product rich in soft stretchability can be obtained. If the difference between the orientation parameters of the two polyamides is less than 0.20 in absolute value, or if the difference between the orientation parameters of the two polyamides in the polyamide composite cross section false twist textured yarn of this embodiment described later is less than 0.05 in absolute value, the fiber does not exhibit crimping property, and a fabric or fiber product rich in soft stretchability cannot be obtained. The difference between the orientation parameters of the two polyamides is preferably high as long as it does not impair the effects of this embodiment, but is preferably 2.00 or less in consideration of the stable manufacturing process of the polyamide composite cross section fiber. If the difference between the orientation parameters of the two polyamides exceeds 2.00, there is a possibility that defects, fluff, etc. may occur in the winding package form.

[0021] Here, the absolute value of the difference in the orientation parameters of two types of polyamide can be calculated by the following formula. Absolute value of the difference in orientation parameters = (orientation parameter of the highly oriented polyamide) - (orientation parameter of the less oriented polyamide)

[0022] In this specification, the highly oriented polyamide refers to the polyamide having the higher orientation parameter value of the two polyamides, and the less oriented polyamide refers to the polyamide having the lower orientation parameter value of the two polyamides.

[0023] In the polyamide composite cross-section fiber of this embodiment, the orientation parameter of the low-orientation polyamide is in the range of 1.50 to 3.00. By setting it in this range, the abrasion resistance of the fiber becomes good, and it is possible to obtain a fabric or fiber product with excellent soft stretchability and significantly improved abrasion resistance, which was difficult to obtain with the conventional technology. If the orientation parameter of the low-orientation polyamide is less than 1.50, the strength and elongation of the fiber is significantly reduced, so that, as with the conventional technology, only fabrics or fiber products with poor abrasion resistance can be obtained even if the crimp performance is excellent. If the orientation parameter of the low-orientation polyamide is more than 3.00, the fiber becomes rigid, so that only fabrics or fiber products with poor abrasion resistance can be obtained even if the crimp performance is excellent.

[0024] Thus, the polyamide composite cross section fiber of this embodiment is not simply a composite of two types of polyamides, but focuses on the orientation characteristics of the polyamide composite cross section fiber, and only by appropriately controlling the orientation parameters of the two types of polyamides can it be possible to obtain a polyamide composite cross section fiber that is excellent in both abrasion resistance and crimp performance. For the control of the orientation parameters of the two types of polyamides, it is important to optimize the spinning draft and draw ratio, and details will be described later.

[0025] There are various methods for measuring the crystallinity of fibers, but the crystallinity of the polyamide composite cross section fiber of this embodiment refers to the crystallinity obtained by converting the half-width of the Raman band from calibration data obtained by laser Raman spectroscopy and X-ray diffraction, and the gist of it is described below.

[0026] Polyamide 1640cm -1 The Raman band around 1640cm is assigned to the stretching vibration mode of C=O, and is also used in the analysis of crystallinity. As the degree of crystallinity increases, the molecular arrangement becomes uniform, and the peak position of the molecular vibration frequency becomes uniform. As a result, the bandwidth becomes sharp, and analyzing the bandwidth is a parameter related to crystallinity. Here, for the polyamide species in question, the 1640cm -1The crystallinity was calculated from the half-width of the Raman band in unpolarized light near the center of the fiber and the peak area ratio of the broad peak indicating amorphous to the sharp peak indicating crystallinity obtained by X-ray diffraction, and calibration data for the band width and crystallinity were prepared. This allows the crystallinity of each component in the polyamide composite cross-section fiber of this embodiment to be calculated using laser Raman spectroscopy, which allows local measurement. The crystallinity will be described in detail in the Examples.

[0027] In the polyamide composite cross-section fiber of this embodiment, the crystallinity of the polyamide on the low orientation side is preferably in the range of 10.0 to 40.0%, more preferably in the range of 20.0 to 35.0%. When the crystallinity of the polyamide on the low orientation side is 10.0% or more, the crystal structure of the polyamide composite cross-section fiber is stabilized, so that stable high-order processing such as false twisting, weaving, knitting, dyeing, etc. is possible even after long-term storage. When the crystallinity of the polyamide on the low orientation side is 40.0% or less, it is possible to further improve abrasion resistance while maintaining crimp performance.

[0028] The polyamide multifilament made of the polyamide composite cross section fiber of this embodiment preferably has a stretch elongation of 1.0% or more. The polyamide multifilament made of the polyamide composite cross section fiber of this embodiment includes so-called drawn yarn obtained by a one-step method, a two-step method, etc., and partially oriented yarn (POY: semi-drawn yarn). The preferable range of the stretching extension rate is different for each, and the preferred stretching extension rate of the drawn yarn is 20.0 to 100.0%, and the preferred stretching extension rate of the POY is 1.00 to 100.0%. Since the preferred stretching extension rate for obtaining a fabric or fiber product having a soft stretchability while maintaining the crimping performance is 20.0% or more, it is preferable that the drawn yarn to be directly input into product processing such as weaving has a stretching extension rate of 20.0% or more. Regarding POY, a stretching extension rate of 20.0% or more is not necessary when input into false twist processing, but if there is a stretching extension rate of 1.0% or more, it is easy to achieve a stretching extension rate of 30.0% or more, which is higher than that of the drawn yarn, when false twist processing is performed. POY having a stretching extension rate of 1.0% or more has, for example, coil shrinkage to the extent that it stretches. The stretching extension rate is preferably high as long as it does not impair the effects of this embodiment, but in consideration of the stable manufacturing process of polyamide composite cross section fiber, it is preferably 100.0% or less. If the stretching extension rate exceeds 100.0%, there is a possibility that defects, fluff, etc. will occur in the wound package form.

[0029] The stretch elongation rate of the polyamide multifilament of the present embodiment is a value measured according to JIS L 1013 (Method C) (2010 edition).

[0030] The single yarn fineness of the polyamide composite cross section fiber of this embodiment is not particularly limited as long as it does not impair the effects of this embodiment, but if the single yarn fineness is in the range of 1.0 to 6.0 dtex, it can be suitably used for innerwear, outerwear, etc. Also, the total fineness of the polyamide multifilament is preferably in the range of 20.0 to 200.0 dtex in consideration of clothing applications.

[0031] The polyamide composite cross section fiber of this embodiment may contain various additives within the range that does not impair the effect of this embodiment. Examples of the additives include pigments such as titanium oxide and carbon black, light resistance agents such as manganese compounds, antioxidants such as hindered phenols and phosphorus compounds, heat resistance agents, flame retardants, conductivity imparting agents, fibrous reinforcing agents, etc.

[0032] The cross-sectional shape of the polyamide composite cross-section fiber of this embodiment may be appropriately selected within a range that does not impair the effects of this embodiment, as long as the composite form is a side-by-side type or an eccentric core-sheath type. In the case of an eccentric core-sheath type as shown in Figure 2, the polyamide (A) 3 of the core component may be a low-orientation side polyamide and the polyamide (B) 4 of the sheath component may be a high-orientation side polyamide, or the polyamide (A) 3 of the core component may be a high-orientation side polyamide and the polyamide (B) 4 of the sheath component may be a low-orientation side polyamide, but preferably the polyamide (A) 3 of the core component is a high-orientation side polyamide and the polyamide (B) 4 of the sheath component is a low-orientation side polyamide. Examples of the cross-section include a perfect circle, an ellipse, a trilobe, a tetralobe, a cross, a hollow, and a flattened cross section, but a perfect circle is preferable from the viewpoint of melt spinnability and ease of spinning.

[0033] As described above, the polyamide multifilament made of the polyamide composite cross section fiber of this embodiment includes drawn yarn and POY: semi-drawn yarn, and by further subjecting these to false twisting, it is possible to further greatly improve both the abrasion resistance and the crimping properties. From the viewpoint of ease of processing, it is preferable to add POY to the false twisting, but it is also possible to further improve the stretching elongation rate by adding the drawn yarn to the false twisting.

[0034] When the composite morphology of the fiber cross section of the polyamide composite cross section fiber of this embodiment is a side-by-side type, the composite morphology of the fiber cross section of the polyamide composite cross section false twisted yarn obtained by false twisting it will also be a side-by-side type, and when the composite morphology of the fiber cross section of the polyamide composite cross section fiber of this embodiment is an eccentric core-sheath type, the composite morphology of the fiber cross section of the polyamide composite cross section false twisted yarn obtained by false twisting it will also be an eccentric core-sheath type.

[0035] In the polyamide composite cross section false twisted yarn of this embodiment, the difference in the orientation parameters of the two polyamides is 0.05 or more in absolute value, preferably 0.09 or more. If the difference in the orientation parameters of the two polyamides is less than 0.05 in absolute value, the crimp is poor and soft stretchability cannot be obtained. In other words, the polyamide composite cross section false twisted yarn is made of composite cross section fibers in which two polyamides (high orientation polyamide and low orientation polyamide) are either of the side-by-side type or eccentric core-sheath type.

[0036] The method for calculating the orientation parameter and the absolute value of the difference in orientation parameters for the polyamide composite cross section false twisted yarn of this embodiment are the same as the method for calculating the orientation parameter and the absolute value of the difference in orientation parameters for the polyamide composite cross section fiber of this embodiment.

[0037] The polyamide composite cross section false twist textured yarn of this embodiment has a stretch extension rate of 30.0% or more, preferably 50.0% or more. A preferred stretch extension rate for obtaining a fabric or fiber product having excellent soft stretchability while maintaining the crimping performance is 20.0% or more, but in order to obtain the ultimate soft stretchability, it is important to false twist the polyamide multifilament made of the polyamide composite cross section fiber of this embodiment to obtain a stretch extension rate of 30.0% or more. In the polyamide composite cross section false twist textured yarn of this embodiment, the orientation characteristics of the precursor polyamide composite cross section fiber are appropriately controlled, and by false twisting it, it is possible to obtain a false twist textured yarn with a higher stretch extension rate. The method for measuring the stretch extension rate of the polyamide composite cross section false twist textured yarn of this embodiment is the same as the method for measuring the stretch extension rate of the polyamide multifilament of this embodiment.

[0038] In the polyamide composite cross section false twisted yarn of this embodiment, the crystallinity of the polyamide on the low orientation side is in the range of 10.0 to 40.0%, preferably in the range of 20.0 to 35.0%. When the crystallinity of the polyamide on the low orientation side is 10.0% or more, the crystal structure of the false twisted yarn is stabilized, so that stable high-order processing, such as weaving, knitting, dyeing, etc., is possible even after long-term storage. When the crystallinity of the polyamide on the low orientation side is 40.0% or less, it is possible to further improve abrasion resistance while maintaining crimp performance. The method for measuring the crystallinity of the polyamide on the low orientation side of the polyamide composite cross section false twisted yarn of this embodiment is the same as the method for measuring the crystallinity of the polyamide on the low orientation side of the polyamide composite cross section fiber of this embodiment.

[0039] The polyamide composite cross-section fiber and polyamide composite cross-section false twist textured yarn of the present embodiment can be woven or knitted according to a known method. The structure of the woven or knitted fabric is not limited. In the case of a woven fabric, the structure may be any of a plain structure, a twill structure, a satin structure, a modified structure thereof, or a mixed structure thereof, depending on the purpose of use. In order to obtain a woven fabric with a firm texture and a fluffy feel, a plain structure with many restraint points, a ripstop structure combining a plain structure with a stone pattern or a nanaco structure, is preferable. In the case of a knitted fabric, the structure may be any of a plain structure, an interlock structure, a half structure, a satin structure, a jacquard structure, a modified structure, or a mixed structure thereof, depending on the purpose of use. In the case of a knitted fabric, the structure may be any of a plain structure, an interlock structure, a half structure, a satin structure, a jacquard structure, a modified structure, or a mixed structure thereof, of a circular knitted fabric, depending on the purpose of use. However, a half structure of a single tricot knitted fabric is preferable because the knitted fabric is thin and stable and has excellent elongation.

[0040] The applications of the woven or knitted fabric of this embodiment are not limited, but are preferably used for clothing, and more preferably for sportswear such as down jackets, windbreakers, golf wear, rainwear, and casual wear, as well as women's and men's clothing.

[0041] Hereinafter, a method for producing the polyamide composite cross section fiber of the present embodiment and the polyamide multifilament made thereof will be described.

[0042] The two polyamides used in the polyamide composite cross-section fiber of this embodiment may be of the same composition or different compositions, but in order to obtain the desired crimping properties, it is preferable to use polyamides of different compositions, for example, polycaproamide and polyhexamethylene sebacamide are one of the preferred combinations. When the composite cross-section fiber is made of polyamides of the same composition, it is sufficient to make a difference in the polymerization degree of both, but this does not apply when the composition difference is caused, for example, by mixing titanium oxide only in one of them. The polyamide composite cross-section fiber described in Patent Document 1 and Patent Document 2 specifies the difference in polymerization degree and melt viscosity of the two preferred polyamides, but these are not particularly important. Even if the polymerization degree and melt viscosity of the two polyamides are exactly the same, it is sufficient to use a combination of polyamides that will cause differences in orientation behavior and crystal structure in the subsequent process, and it is more important to appropriately control the spinning draft and draw ratio described below.

[0043] The melting part of the manufacturing process will be described. When melting two kinds of polyamides, the pressure melter method or the extruder method can be mentioned, but is not particularly limited. The melting temperature can be appropriately determined in consideration of the melting point of the polyamide resin, but it is preferable to melt the two kinds of polyamides separately at a temperature 20 to 60°C higher than the melting point. The spinning temperature may be appropriately determined in consideration of the melting point of the polyamide resin, similarly to the melting temperature. The spinning temperature here refers to the so-called heat retention temperature (spin block temperature) at which the polymer piping, metering pump, spinneret, etc. are kept warm.

[0044] In the method for producing the polyamide bicomponent cross section fiber and the polyamide multifilament made thereof according to the present embodiment, it is important to appropriately control the spinning draft and the draw ratio. From the viewpoint of controlling these, the direct spinning and drawing method is excellent, and the production method using the direct spinning and drawing method will be exemplified below.

[0045] As shown in FIG. 4, two kinds of polyamides melted separately are metered and fed to a conjugate spinneret 9 forming a side-by-side type or an eccentric sheath-core type. Here, the two kinds of polyamides join together and are discharged from a nozzle 10 of the spinneret as a side-by-side type or an eccentric sheath-core type polyamide conjugate cross section fiber. In the case of the side-by-side type where the conjugate interface is a straight line, it is preferable to discharge the thread, i.e., the polyamide conjugate cross section fiber, by disposing the two kinds of polyamides so that the conjugate interface 11 is parallel to the direction of the thread cooling air 8, which will be described later, from a thread cooling device such as a chimney 7, as shown in FIG. 4(A). In the case of the side-by-side type where the conjugate interface is a curve, it is preferable to discharge the thread by disposing the two kinds of polyamides so that the straight line connecting the ends of the two points of the conjugate interface is parallel to the direction of the thread cooling air, and in the case of the eccentric sheath-core type where the longitudinal direction of the core component polyamide is parallel to the direction of the thread cooling air. As for the arrangement of the two kinds of polymers, as described in, for example, Japanese Patent No. 3769434 (JP Patent Publication 2000-328349) and the like, it is common from the viewpoint of expressing the crimping performance to arrange the high shrinkage (high orientation side) polymer 14 on the windward side of the yarn cooling air 8 and the low shrinkage (low orientation side) polymer 15 on the leeward side of the yarn cooling air 8 as shown in (B) of Fig. 4, but in this method, since the low shrinkage polymer 15 is not cooled easily, the spinning stress is concentrated only on the high shrinkage polymer 14, and the spun yarn may break, which may be undesirable from the viewpoint of spinning operability. Here, the high shrinkage (high orientation side) polymer 14 corresponds to the high orientation side in this embodiment, and the low shrinkage (low orientation side) polymer 15 corresponds to the low orientation side in this embodiment. In this embodiment, improvements in crimp performance and abrasion resistance are achieved by appropriately controlling the spinning draft and draw ratio described below. In this system, as shown in FIG. 4(A), it is preferable from the viewpoint of spinning operability to discharge two types of polyamide so that the composite interface 11 is parallel to the direction of the yarn cooling air 8 and to cool the two types of polyamide evenly.

[0046] The discharged yarn is sucked to remove gaseous low polymer components from the yarn (MO suction), and then cooled to room temperature by blowing cooling air onto the yarn using a yarn cooling device such as a chimney, and then oiled and bundled using an oiling device, and entangled using a fluid treatment device. If necessary, the yarn is oiled and bundled again using an oiling device, receives an appropriate spinning draft using a take-up roller, and passes through a stretching roller, during which it is appropriately stretched according to the ratio of the peripheral speeds of the take-up roller and the stretching roller. It is highly preferable to heat set the fiber after drawing, whether it is a drawn yarn or a POY:semi-drawn yarn, and then it is wound up using a winding device.

[0047] In the present embodiment, the polyamide composite cross section fiber and the method for producing the polyamide multifilament made thereof have a spinning draft of preferably 100 to 300, more preferably 150 to 250. The term "spinning draft" refers to the peripheral speed of the take-up roller divided by the linear discharge speed of the die. The term "linear discharge speed of the die" refers to the discharge volume (volume) calculated by dividing the discharge mass per die discharge hole by the density of the molten polymer, and then divided by the cross-sectional area of ​​the die discharge hole. By setting the spinning draft within this range, the orientation characteristics of the two polyamides in this embodiment can be appropriately controlled, making it possible to obtain polyamide composite cross section fibers having excellent abrasion resistance and crimping performance, and fabrics and textile products having excellent soft stretchability can be obtained. When the spinning draft is less than 100, the difference in the orientation parameters of the two polyamides is not obtained, so that the crimping property of the fiber is not expressed, and fabrics and textile products having excellent soft stretchability tend not to be obtained. When the spinning draft exceeds 300, the orientation parameter of the polyamide on the low orientation side becomes high, so that the fiber becomes rigid, and as in the conventional technology, even if the crimping performance is excellent, only fabrics or fiber products with poor abrasion resistance can be obtained.

[0048] The stretching ratio is preferably in the range of 1.05 to 2.40 times, more preferably in the range of 1.07 to 2.00 times. The "stretching ratio" here is the value obtained by dividing the peripheral speed of the stretching roller by the peripheral speed of the take-up roller. By setting the stretching ratio in this range, the orientation characteristics of the two types of polyamide in this embodiment can be appropriately controlled, so that a polyamide composite cross-section fiber excellent in both abrasion resistance and crimping performance can be obtained, and a fabric or textile product rich in soft stretchability can be obtained. When the stretching ratio is less than 1.05 times, the orientation does not proceed and the orientation parameter becomes small, so that the crimping property of the fiber does not appear, and it tends not to be possible to obtain a fabric or textile product rich in soft stretchability. In addition, the orientation parameter of the polyamide on the low orientation side also becomes small, so that the strength and elongation of the fiber decreases, and the practical durability when made into a fabric or textile product tends to decrease significantly. When the draw ratio exceeds 2.40 times, the orientation parameter of the polyamide on the low orientation side becomes high, so that the fiber becomes rigid, and as in the conventional technology, even if the crimp performance is excellent, only fabrics or fiber products with poor abrasion resistance tend to be obtained.

[0049] Regarding heat setting, it is preferable to heat set the drawn yarn and the POY: semi-drawn yarn. The heat setting temperature is preferably in the range of 100 to 200 ° C, more preferably in the range of 130 to 190 ° C. If the heat setting temperature is 100 ° C or higher, the orientation parameter obtained by appropriately controlling the spinning draft and the draw ratio is not relaxed, and as a result, the difference in the orientation parameters of the two polyamides can be maintained, the crimping property of the fiber is expressed, and a fabric or fiber product rich in soft stretchability can be obtained. In addition, the crystallinity of the polyamide on the low orientation side is also high, so that the crystal structure is stable, and stable high-order processing (false twisting, weaving, knitting, dyeing, etc.) is possible even after long-term storage. If the heat setting temperature is 200 ° C or lower, the orientation parameter of the polyamide on the low orientation side is low, so that the softness of the fiber can be maintained, and a fabric or fiber product excellent in both soft stretchability and abrasion resistance can be obtained.

[0050] As described above, the polyamide multifilament made of the polyamide composite cross section fiber of this embodiment includes drawn yarn and POY: semi-drawn yarn, but it is preferable to heat set the POY as well as described above. Usually, polyamide POY is not often heat set. This is because heat setting at the POY stage promotes crystallization of the fiber and reduces the amorphous distortion portion that is subject to twist deformation, and the crimp performance of the false twist textured yarn obtained in this way is low. However, in the two types of polyamide in this embodiment, control of the orientation parameters is more important, and it is preferable to heat set the POY as well in order to appropriately control the orientation parameters.

[0051] As an example of the heat setting method, in the case of the direct spin-drawing method, the yarn is brought into contact with a heater after drawing, and a method is preferably used in which a heater is provided inside the drawing roller and the yarn held (contacted) by the drawing roller is heat set.

[0052] The winding speed may be appropriately set within a range in which various parameters of the two types of polyamide in this embodiment, such as the orientation parameter, crystallinity, and stretch elongation rate, fall within the desired range and stable production is possible, but a range of 3000 to 5000 m / min is preferable. The polyamide composite cross-section false twist textured yarn of the present embodiment can be obtained by a conventionally known false twist texture technique, and is preferably false twist textured by a draw-friction false twist texture device.

[0053] Examples are as follows. For example, the false twist polyamide yarn of this embodiment supplied to the draw-friction false twist texturing device is sent to a feed roller via a desired yarn guide and fluid treatment device. It is then guided to a draw roller through a heated false twist heater, a cooling plate, and a twisting body that performs draw-friction false twisting, and wound up as a false twist textured yarn. As for the draw-friction false twisting, the yarn may be subjected to friction false twisting after being stretched by a hot pin or hot plate before the feed roller of the draw-friction false twist texturing device, or may be subjected to friction false twisting while being stretched between the feed roller and the stretch roller.

[0054] The twisting body is not limited to a pin type, a friction type, a belt nip type, etc. When it is desired to strengthen the crimp, it is preferable to use the pin type, and when it is desired to increase the processing speed and reduce the production cost, it is preferable to use the friction type or the belt nip type.

[0055] The heating method may be a high-temperature contact heater or a high-temperature non-contact heater, but is not limited thereto. In order to obtain high shrinkage performance, it is necessary to apply heat firmly to the yarn with a high-temperature contact heater to rearrange the molecules in the fiber and relieve the distortion. Therefore, a high-temperature contact heater is preferable, and the processing temperature, i.e., the heater setting temperature of the contact type hot plate, is preferably 170 to 200°C.

[0056] The cooling method includes, but is not limited to, a method using a cooling plate, air cooling, water cooling, etc. Among the methods using a cooling plate, air cooling, and water cooling, the water cooling method has the highest cooling efficiency but causes the most damage to the yarn, and the air cooling method has the lowest cooling efficiency but causes the least damage to the yarn. Note that the water cooling method tends to have a complicated process and poor productivity. Considering efficiency and damage to the yarn, it is preferable to use a cooling plate.

[0057] The ratio of the untwisting tension T2 to the twisting tension T1 (T2 / T1) is preferably 0.7 to 1.0. When T2 / T1 is 1.0 or less, that is, when the untwisting tension T2 is small, the generation of fuzz, that is, single yarn breakage, can be suppressed, so that yarn breakage after the twisting body is reduced, stable stretch friction false twisting processing is possible, and the obtained false twisted yarn has excellent quality. By making T2 / T1 0.7 or more, poor untwisting can be suppressed, so that high crimp can be obtained. Here, the twisting tension is the tension at the part where the twist is applied upstream of the twisting body, and the untwisting tension is the tension at the part where the twist is unwound downstream of the twisting body. The twisting tension and the untwisting tension can be measured by a tension meter.

[0058] The ratio of the surface speed D of the twisting body to the speed Y of the stretching roller, which is the yarn running speed (D / Y ratio), is preferably 1.0 to 2.0. By making the D / Y ratio 1.0 or more, the balance between the twisting tension T1 and the untwisting tension T2 is good, and it is possible to perform stretch-friction false twisting without fluff or yarn breakage. Furthermore, by making the D / Y ratio 2.0 or less, the surface wear of the twisting body is suppressed, and the quality of the yarn in the longitudinal direction is stable even during continuous operation for several tens of hours, and stretch-friction false twisting without fluff or yarn breakage is realized. EXAMPLES

[0059] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples. The methods for measuring the properties in the examples are as follows.

[0060] A. Orientation parameters Measurements were performed by Raman spectroscopy using a Jobin Yvon / Atago Bussan T-64000 under the following conditions: measurement mode: microscopic Raman, objective lens: ×100, beam diameter: 1 μm, light source: Ar+ laser / 514.5 nm, laser power: 100 mW, diffraction grating: Single 600, 1800 gr / mm, slit: 100 μm, detector: Jobin Yvon CCD 1024 × 256.

[0061] For the measurement sample, a single yarn was taken from the multifilament and fixed in a curled state according to the crimp of the single yarn. The inside of the curl was the highly oriented polyamide, and the outside was the less oriented polyamide. Analysis was performed by irradiating polarized light perpendicular to each component. The irradiated polarized light was parallel (||) to the longitudinal direction of the fiber, and perpendicular (⊥) to the longitudinal direction. The 1640 cm wavelength, which is assigned to the stretching vibration mode of C=O of polyamide, was observed. -1 Raman bands around 1450 cm, which are assigned to the CH bending band -1 The Raman bands in the vicinity were read for each component and each polarization, and the following formula was used to calculate. Note that the measurements were performed on five single yarns randomly taken from the multifilament, and the calculation was performed using the average value of three measurements for each component of each single yarn (highly oriented polyamide, lowly oriented polyamide). Orientation parameter = (I 1640 / I 1450 ) Vertical polarization / (I 1640 / I 1450 ) Parallel polarization Absolute value of the difference in orientation parameters=(orientation parameter of the highly oriented polyamide)−(orientation parameter of the less oriented polyamide).

[0062] B. Crystallinity Measurements were performed by Raman spectroscopy using a Jobin Yvon / Atago Bussan T-64000 under the following conditions: measurement mode: microscopic Raman, objective lens: ×100, beam diameter: 1 μm, light source: Ar+ laser / 514.5 nm, laser power: 100 mW, slit: 100 μm, detector: Jobin Yvon CCD 1024 × 256. The measurement sample was a single yarn taken from the multifilament and fixed in a curled state according to the crimp of the single yarn. The outside of the curl was treated as the low orientation side, and the analysis was performed by irradiating the curled outer component with light perpendicularly. -1 The half-width of the Raman band near the center was read and converted into the crystallinity of the low-oriented polyamide. The half-width was converted into the crystallinity by preparing polyamide single yarns with different crystallinity in advance, measuring the half-width and XRD to create a calibration curve, and then converting the data. The measurement was performed on five single yarns randomly taken from the multifilament, and the calculation was performed using the average value of three measurements of the low-oriented polyamide component of each single yarn.

[0063] C.Stretching and elongation rate The stretching and elongation rates were measured according to JIS L 1013 (Method C) (2010 edition), except that the heat treatment method was to treat the material in hot water at a temperature of 90°C for 20 minutes without applying a load.

[0064] D. Total size, single yarn size A yarn sample was set on a measuring machine with a circumference of 1 m and rotated 250 times to make a looped skein. After drying in a hot air dryer (105±2°C x 60 minutes), the mass of the skein was weighed on a weighing scale and multiplied by the official moisture content to calculate the total fineness. The official moisture content was set to a uniform 4.5%. The single yarn fineness was calculated by dividing the calculated total fineness by the number of filaments.

[0065] E. Relative viscosity of 98% sulfuric acid 0.25 g of the sample was dissolved in 100 ml of 98% sulfuric acid to give a total weight of 1 g, and the flow time T1 was measured at 25°C using an Ostwald viscometer. Subsequently, the flow time T2 of only the 98% sulfuric acid was measured. The ratio of T1 to T2, i.e., T1 / T2, was determined as the relative viscosity of 98% sulfuric acid.

[0066] F. Stretch fabric According to JIS L 1096 (Method A) (constant speed extension method: 2010 edition), an Instron tensile tester was used to measure the elongation rate when a sample with a width of 50 mm x 300 mm in the warp and weft directions was elongated to 14.7 N at a tensile speed of 200 mm / min with a gripping distance of 200 mm. The measurement results were categorized as follows, with ◎ and ○ indicating pass. ◎: 25.0% or more ○: 15.0% or more and less than 25.0% △: 10.0% or more and less than 15.0% ×: Less than 10.0%.

[0067] G. Fabric abrasion resistance (Martindale method) Abrasion resistance was measured according to JIS L 1096 (Method A) (friction strength: 2010 edition) Method E. The measurement results were categorized as follows, with ◎ and ○ indicating pass. ◎:5th grade ○: Grade 4 or above, but below grade 5 △: Grade 3 or above, but below grade 4 ×: Below grade 3.

[0068] Examples 1 to 4, 6, and 7, Comparative Examples 3 to 5 Polycaproamide (relative viscosity in 98% sulfuric acid: 3.25, chip moisture content: 100 ppm) as the core component polyamide (A) was melted at 290°C, and polyhexamethylenesebacamide (relative viscosity in 98% sulfuric acid: 2.70, chip moisture content: 1500 ppm) as the sheath component polyamide (B) was melted at 270°C in a pressure melter, and extruded using an eccentric core-sheath composite spinneret (24 holes x 2 groups, round holes). In this specification, polycaproamide is also referred to as N6, and polyhexamethylenesebacamide is also referred to as N610.

[0069] The area ratio of polyamide (A) to polyamide (B) (polyamide A / polyamide B), L / M when the line segment between the center of the entire composite cross section fiber and the center of the core is L and the line segment between the intersection points of a straight line extending line L and the outer periphery of the composite cross section fiber is M, and the spinning draft are as shown in Table 1.

[0070] Polyamide (A) and polyamide (B) were arranged and discharged so that the direction of the yarn cooling air was parallel to the direction of the composite interface. The discharged yarn was sucked by MO, and cooling air (wind speed 30 m / min, air temperature 20°C) was blown onto it by a uniflow chimney to cool and solidify the yarn to room temperature. The cooled and solidified yarn was oiled with a water-containing oil agent by an oiling device, then entangled with a fluid treatment device, and oiled again with a water-containing oil agent by an oiling device.

[0071] Regarding the drawing, the peripheral speed of the take-up roller, the peripheral speed of the drawing roller, and the draw ratio are as shown in Table 1. Regarding the heat setting, a heater was provided inside the drawing roller and the drawing roller was brought into contact with the drawing roller, and the surface temperature of the drawing roller (heat setting temperature) is as shown in Table 1. After drawing and heat setting, the fiber was taken up by a winder to obtain a multifilament consisting of a polyamide eccentric core-sheath cross section fiber of 66 dtex and 24 filaments.

[0072] The obtained polyamide eccentric sheath-core cross section fiber was measured for the orientation parameters of the polyamide on the low and high orientation sides, the difference in the orientation parameters (absolute value), the crystallinity of the polyamide on the low orientation side, the stretch elongation rate, the total fineness, and the single yarn fineness. In addition, the number of yarn breakages when 1 ton of polyamide eccentric sheath-core cross section fiber was produced was also counted. These results are shown in Table 1.

[0073] The obtained multifilament was subjected to simultaneous drawing and false twisting processing using a friction type drawing and friction false twisting device at a processing temperature (contact type hot plate heater setting temperature) of 160°C, a draw ratio of 1.25, a D / Y ratio of 1.95, and T2 / T1 = 0.81 to obtain a false twist textured yarn of approximately 56 dtex and 24 filaments. The orientation parameter difference, the crystallinity of the polyamide on the low orientation side, the stretch extension rate, and the total fineness of the obtained false twist textured yarn were measured. These results are shown in Table 1. The composite form of the false twist textured yarn was the same as that of the polyamide composite cross section fiber used in the production of the false twist textured yarn.

[0074] The resulting false twist textured yarn was used to produce a plain weave fabric with a warp density of 116 threads / 2.54 cm and a weft density of 84 threads / 2.54 cm. The fabric was then scouring and dyeing processed using a liquid jet, and the dry heat setting of the fabric was appropriately adjusted. The fabric stretch and abrasion resistance (Martindale method) of the resulting fabric were measured. The results are shown in Table 1.

[0075] [Table 1]

[0076] Example 5 Except for not heat setting after drawing, the polymer composition, temperature, and composite form were the same as in Example 1, and the other conditions were as shown in Table 2. Melt spinning was performed to obtain a polyamide eccentric sheath-core cross section fiber of 66 dtex and 24 filaments. For the obtained polyamide eccentric sheath-core cross section fiber, the orientation parameters of the low and high orientation polyamides, the difference in orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch extension rate, the total fineness, and the single yarn fineness were measured. In addition, the number of yarn breakages when 1 ton of polyamide eccentric sheath-core cross section fibers was produced was also counted. These results are shown in Table 2. The obtained polyamide eccentric core-sheath cross section fiber was false-twisted in the same manner as in Example 1 to obtain a false-twisted yarn of about 56 dtex and 24 filaments. The orientation parameter difference, the crystallinity of the polyamide on the low orientation side, the stretch extension rate, and the total fineness of the obtained false-twisted yarn were measured. The results are shown in Table 2. The false twist textured yarn thus obtained was subjected to the same high-level processing as in Example 1 to obtain a fabric. The fabric stretch and fabric abrasion resistance (Martindale method) of the obtained fabric were measured. The results are shown in Table 2.

[0077] Comparative Example 1 Polyhexamethylene adipamide (relative viscosity in 98% sulfuric acid: 2.63, chip moisture content: 1100 ppm) was melted at 290°C in a pressure melter and discharged using a spinneret (24 holes x 2 groups, round holes), and melt spun in the same manner as in Example 1, except that heat setting after drawing was not performed, to obtain a polyhexamethylene adipamide fiber of about 66 dtex and 24 filaments. In this specification, polyhexamethylene adipamide is also referred to as N66. The obtained polyhexamethylene adipamide fiber was measured for the stretch elongation, total fineness, and single yarn fineness. The number of yarn breakages per ton of polyhexamethylene adipamide fiber produced was also counted. The results are shown in Table 2. The obtained polyhexamethylene adipamide fiber was false-twisted in the same manner as in Example 1, except that the processing temperature was 195°C, to obtain a false-twisted yarn of about 56 dtex and 24 filaments. The stretch elongation and total fineness of the obtained false-twisted yarn were measured. The results are shown in Table 2. The false twist textured yarn thus obtained was subjected to the same high-level processing as in Example 1 to obtain a fabric. The fabric stretch and fabric abrasion resistance (Martindale method) of the obtained fabric were measured. The results are shown in Table 2.

[0078] Comparative Example 2 Polycaproamide (relative viscosity in 98% sulfuric acid: 3.25, chip moisture content: 100 ppm) was used as the core component polyamide (A) at 290°C, and polyhexamethylenesebacamide (relative viscosity in 98% sulfuric acid: 2.70, chip moisture content: 1500 ppm) was used as the sheath component polyamide (B) at 270°C. They were melted in a pressure melter and extruded using a double core-sheath (concentric) composite spinneret (24 holes x 2 groups, round holes) in the same manner as in Example 1, to obtain a polyamide double core-sheath (concentric) cross section fiber of approximately 66 dtex and 24 filaments. The obtained polyamide double core-sheath (concentric circle) cross section fiber was measured for the stretch elongation rate, total fineness, and single yarn fineness. In addition, the number of yarn breakages when one ton of polyamide double core-sheath (concentric circle) cross section fiber was produced was also counted. These results are shown in Table 2. The obtained polyamide double core-sheath (concentric circle) cross section fiber was false twisted in the same manner as in Example 1 to obtain a false twist textured yarn of about 56 dtex and 24 filaments. The stretch elongation and total fineness of the obtained false twist textured yarn were measured. The results are shown in Table 2. The false twist textured yarn thus obtained was subjected to the same high-level processing as in Example 1 to obtain a fabric. The fabric stretch and fabric abrasion resistance (Martindale method) of the obtained fabric were measured. The results are shown in Table 2.

[0079] Example 8 Melt spinning was performed in the same manner as in Example 1, except that polyamide (A) and polyamide (B) were arranged so that the direction of the yarn cooling air and the direction of the composite interface were perpendicular (polyamide (A) on the windward side of the cooling air, and polyamide (B) on the leeward side), to obtain a polyamide eccentric core-sheath cross section fiber of approximately 66 dtex and 24 filaments. The obtained polyamide eccentric sheath-core cross section fibers were measured for the orientation parameters of the low and high orientation polyamides, the difference in the orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch elongation rate, the total fineness, and the single fiber fineness. In addition, the number of yarn breakages when 1 ton of polyamide eccentric sheath-core cross section fibers was produced was also counted. These results are shown in Table 2. The obtained polyamide eccentric core-sheath cross section fiber was false-twisted in the same manner as in Example 1 to obtain a false-twisted yarn of about 56 dtex and 24 filaments. The orientation parameter difference, the crystallinity of the polyamide on the low orientation side, the stretch extension rate, and the total fineness of the obtained false-twisted yarn were measured. The results are shown in Table 2. The false twist textured yarn thus obtained was subjected to the same high-level processing as in Example 1 to obtain a fabric. The fabric stretch and fabric abrasion resistance (Martindale method) of the obtained fabric were measured. The results are shown in Table 2.

[0080] Example 9 The polyamide (A) core component was polycaproamide (relative viscosity in 98% sulfuric acid: 3.25, chip moisture content: 100 ppm) at 290°C, and the polyamide (B) sheath component was polyhexamethylene adipamide (relative viscosity in 98% sulfuric acid: 2.63, chip moisture content: 1100 ppm) at 290°C. Except for this, each was melted in a pressure melter in the same manner as in Example 1 to obtain a polyamide eccentric core-sheath cross section fiber of approximately 66 dtex and 24 filaments. The obtained polyamide eccentric sheath-core cross section fibers were measured for the orientation parameters of the low and high orientation polyamides, the difference in the orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch elongation rate, the total fineness, and the single fiber fineness. In addition, the number of yarn breakages when 1 ton of polyamide eccentric sheath-core cross section fibers was produced was counted. These results are shown in Table 1. The obtained polyamide eccentric core-sheath cross section fiber was false-twisted in the same manner as in Example 1 to obtain a false-twisted yarn of about 56 dtex and 24 filaments. The orientation parameter difference, the crystallinity of the polyamide on the low orientation side, the stretch extension rate, and the total fineness of the obtained false-twisted yarn were measured. The results are shown in Table 2. The false twist textured yarn thus obtained was subjected to the same high-level processing as in Example 1 to obtain a fabric. The fabric stretch and fabric abrasion resistance (Martindale method) of the obtained fabric were measured. The results are shown in Table 2.

[0081] Example 10 Polycaproamide (relative viscosity in 98% sulfuric acid: 3.25, chip moisture content: 100 ppm) as the core component polyamide (A) was melted at 290°C, and polycaproamide (relative viscosity in 98% sulfuric acid: 2.10, chip moisture content: 100 ppm) as the sheath component polyamide (B) was melted at 270°C in a pressure melter, and melt spinning was performed in the same manner as in Example 1 to obtain a polyamide eccentric core-sheath cross section fiber of approximately 66 dtex and 24 filaments. The obtained polyamide eccentric sheath-core cross section fibers were measured for the orientation parameters of the low and high orientation polyamides, the difference in the orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch elongation rate, the total fineness, and the single fiber fineness. In addition, the number of yarn breakages when 1 ton of polyamide eccentric sheath-core cross section fibers was produced was also counted. These results are shown in Table 2. The obtained polyamide eccentric core-sheath cross section fiber was false-twisted in the same manner as in Example 1 to obtain a false-twisted yarn of about 56 dtex and 24 filaments. The orientation parameter difference, the crystallinity of the polyamide on the low orientation side, the stretch extension rate, and the total fineness of the obtained false-twisted yarn were measured. The results are shown in Table 2. The false twist textured yarn thus obtained was subjected to the same high-level processing as in Example 1 to obtain a fabric. The fabric stretch and fabric abrasion resistance (Martindale method) of the obtained fabric were measured. The results are shown in Table 2.

[0082] [Table 2]

[0083] Examples 11 to 15, Comparative Examples 6 to 8 As polyamide (A), polycaproamide (relative viscosity in 98% sulfuric acid: 2.63, chip moisture content: 100 ppm) was melted at 275°C, and as polyamide (B), polyhexamethylenesebacamide (relative viscosity in 98% sulfuric acid: 2.70, chip moisture content: 1500 ppm) was melted at 260°C in a pressure melter, and extruded using a side-by-side composite spinneret (24 holes x 2 groups, round holes). Melt spinning was performed in the same manner as in Example 1, except that the melt spinning process shown in Table 3 was performed, to obtain a polyamide side-by-side cross section fiber of approximately 63 dtex and 24 filaments. The obtained polyamide side-by-side cross section fiber was measured for the orientation parameters of the low and high orientation polyamides, the difference in the orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch elongation rate, the total fineness, and the single yarn fineness. In addition, the number of yarn breakages when 1 ton of polyamide side-by-side cross section fiber was produced was also counted. These results are shown in Table 3. The obtained polyamide side-by-side cross section fiber and the obtained multifilament were subjected to simultaneous drawing and false twisting processing using a pin-type drawing friction false twisting device at a processing temperature (contact type hot plate heater setting temperature) of 190°C, a draw ratio of 1.20, a D / Y ratio of 1.95, and T2 / T1 = 0.81 to obtain a false twist textured yarn of about 56 dtex and 24 filaments. The orientation parameter difference, the crystallinity of the polyamide on the low orientation side, the stretch extension rate, and the total fineness of the obtained false twist textured yarn were measured. These results are shown in Table 3. The false twist textured yarn thus obtained was subjected to the same high-level processing as in Example 1 to obtain a fabric. The fabric stretch and fabric abrasion resistance (Martindale method) of the obtained fabric were measured. The results are shown in Table 3.

[0084] [Table 3]

[0085] Examples 16 to 21, Comparative Examples 9 to 11 Melt spinning was carried out in the same manner as in Example 1 to obtain a polyamide eccentric sheath-core cross section fiber of approximately 56 dtex and 24 filaments by the melt spinning process shown in Table 4. For the obtained polyamide eccentric sheath-core cross section fiber, the orientation parameters of the low and high orientation polyamides, the difference in orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch elongation rate, the total fineness, and the single yarn fineness were measured. In addition, the number of yarn breakages when 1 ton of polyamide eccentric sheath-core cross section fibers was produced was also counted. These results are shown in Table 4. The obtained polyamide eccentric core-sheath cross section fiber was not false twisted, but was subjected to the same high-level processing as in Example 1 to obtain a fabric. The obtained fabric was measured for fabric stretch and fabric abrasion resistance (Martindale method). The results are shown in Table 4.

[0086] [Table 4]

[0087] Example 22 Melt spinning was performed in the same manner as in Example 1, except that polyamide (A) and polyamide (B) were arranged so that the direction of the yarn cooling air and the direction of the composite interface were perpendicular (polyamide (A) on the windward side of the cooling air, and polyamide (B) on the leeward side), to obtain a polyamide eccentric sheath-core type cross section fiber of about 56 dtex and 24 filaments. For the obtained polyamide eccentric sheath-core type cross section fiber, the orientation parameters of the low and high orientation polyamides, the difference in orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch elongation rate, the total fineness, and the single yarn fineness were measured. In addition, the number of yarn breakages when 1 ton of polyamide eccentric sheath-core type cross section fiber was produced was also counted. These results are shown in Table 5. The obtained polyamide eccentric core-sheath cross section fiber was not false twisted, but was subjected to the same high-level processing as in Example 1 to obtain a fabric. The obtained fabric was measured for fabric stretch and fabric abrasion resistance (Martindale method). The results are shown in Table 5.

[0088] Example 23 The polyamide (A) core component was polycaproamide (relative viscosity in 98% sulfuric acid: 3.25, chip moisture content: 100 ppm) and the polyamide (B) sheath component was polyhexamethylene adipamide (relative viscosity in 98% sulfuric acid: 2.63, chip moisture content: 1100 ppm) melted at 270°C in a pressure melter, respectively, and melt spinning was performed in the same manner as in Example 1 to obtain a polyamide eccentric core-sheath cross section fiber of approximately 66 dtex and 24 filaments. The obtained polyamide eccentric sheath-core cross section fibers were measured for the orientation parameters of the low and high orientation polyamides, the difference in the orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch elongation rate, the total fineness, and the single fiber fineness. In addition, the number of yarn breakages when 1 ton of polyamide eccentric sheath-core cross section fibers was produced was also counted. These results are shown in Table 5.

[0089] Example 24 Polycaproamide (relative viscosity in 98% sulfuric acid: 3.25, chip moisture content: 100 ppm) as the core component polyamide (A) was melted at 290°C, and polycaproamide (relative viscosity in 98% sulfuric acid: 2.10, chip moisture content: 100 ppm) as the sheath component polyamide (B) was melted at 270°C in a pressure melter, and melt spinning was performed in the same manner as in Example 1 to obtain a polyamide eccentric core-sheath cross section fiber of approximately 66 dtex and 24 filaments. The obtained polyamide eccentric sheath-core cross section fibers were measured for the orientation parameters of the low and high orientation polyamides, the difference in the orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch elongation rate, the total fineness, and the single fiber fineness. In addition, the number of yarn breakages when 1 ton of polyamide eccentric sheath-core cross section fibers was produced was also counted. These results are shown in Table 5. The obtained polyamide eccentric core-sheath cross section fiber was not false twisted, but was subjected to the same high-level processing as in Example 1 to obtain a fabric. The obtained fabric was measured for fabric stretch and fabric abrasion resistance (Martindale method). The results are shown in Table 5.

[0090] Examples 25 to 28, Comparative Examples 12 to 14 As polyamide (A), polycaproamide (relative viscosity in 98% sulfuric acid: 2.63, chip moisture content: 100 ppm) was melted at 275°C, and as polyamide (B), polyhexamethylenesebacamide (relative viscosity in 98% sulfuric acid: 2.70, chip moisture content: 1500 ppm) was melted at 260°C in a pressure melter, and extruded using a side-by-side composite spinneret (24 holes x 2 groups, round holes) under the conditions shown in Table 6. The melt spinning was carried out in the same manner as in Example 1 to obtain a polyamide side-by-side cross section fiber of about 56 dtex and 24 filaments. The obtained polyamide side-by-side cross section fiber was measured for the orientation parameters of the low and high orientation polyamides, the difference in the orientation parameters (absolute value), the crystallinity of the low orientation polyamide, the stretch elongation rate, the total fineness, and the single yarn fineness. In addition, the number of yarn breakages when 1 ton of polyamide side-by-side cross section fiber was produced was also counted. These results are shown in Table 6. The obtained polyamide side-by-side cross section fiber was not false-twisted, but was subjected to the same high-level processing as in Example 1 to obtain a fabric. The obtained fabric was measured for fabric stretch and fabric abrasion resistance (Martindale method). The results are shown in Table 6.

[0091] [Table 5]

[0092] [Table 6]

[0093] As is clear from the results in Tables 1 to 6, the polyamide conjugated cross section fiber of this embodiment has extremely remarkable effects in terms of being excellent in both abrasion resistance and crimp properties compared to conventional polyamide conjugated cross section fibers.

[0094] Although the present invention has been described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2023-010788) filed on January 27, 2023, and is incorporated by reference in its entirety. In addition, all references cited herein are incorporated in their entirety. [Explanation of symbols]

[0095] 1: Polyamide (A) 2: Polyamide (B) 3: Polyamide core component (A) 4: Polyamide sheath component (B) 5: Center of the core component 6: Center of composite cross-section fiber 7: Chimney 8: Yarn cooling air 9: Composite spinneret 10: nozzle outlet 11: Composite interface 12: Polyamide (A) 13: Polyamide (B) 14: High shrinkage (high orientation) polymer 15: Low shrinkage (low orientation side) polymer

Claims

1. A polyamide bicomponent cross-section fiber made of two types of polyamides, which satisfies the following items A to C: A. The composite form of the fiber cross section of the polyamide composite cross section fiber is a side-by-side type or an eccentric core-sheath type. B. The difference in orientation parameters between the two polyamides is 0.20 or more in absolute value. C. The orientation parameter of the low-oriented polyamide is in the range of 1.50 to 3.

00.

2. 2. The polyamide fiber according to claim 1, wherein the crystallinity of the polyamide on the low orientation side is in the range of 10.0 to 40.0%.

3. 3. A polyamide multifilament comprising the polyamide bicomponent cross section fiber according to claim 1 or 2, and having a stretch elongation of 1.0% or more.

4. A polyamide composite cross-section false twist textured yarn comprising two types of polyamide, which satisfies the following items D to G. D. The composite form of the fiber cross section of the polyamide composite cross section false twist textured yarn is a side-by-side type or an eccentric core-sheath type. E. The stretch elongation of the polyamide composite cross section false twisted yarn is 30.0% or more. F. The difference in orientation parameters between the two polyamides is 0.05 or more in absolute value. G. The crystallinity of the low-oriented polyamide is in the range of 10.0 to 40.0%.

Citation Information

Patent Citations

  • JP1971-037767A

  • Felt for paper manufacturing machine and preparation thereof

    JP1993214694A

  • Method for producing conjugate fiber and spinneret for conjugate spinning

    JP2001279520A

  • Conjugated polyamide fiber for false twisting

    JP2018003190A

  • Polyamide latent crimped yarn and method for manufacturing same

    WO2015151220A1